First Day Cover commemorating Peace Day in Hiroshima (1949)
Philatelic cachet is an offset lithograph depicting an atomic model floating above the Earth with the text "Peace Forever" heading the illustration. Designates August 6th as Peace Day in Hiroshima in memoriam of the 140,000 people who died after the first atomic bomb, Little Boy, was dropped on Hiroshima on August 6, 1945. Printed text on the envelope states "Proclaiming Hiroshima as the City of Eternal Peace 1949" and "Postal Stamps Exhibition of Peace Hiroshima (H.P.S.)." Stamp depicts a seated person.
Keywords: Offset lithography; Postage stamps; Postmarks; Commemorative postage stamps; Japan--Hiroshima-shi; Peace Day; Bombardment of Hiroshima-shi (Hiroshima-shi, Japan : 1945); Atomic bomb; Bombings; Nuclear warfare